Dental changes and space gained as a result of early treatment of pseudo-Class III malocclusion - Gu Yan; Rabie A. Bakr M. (Sciendo, 2000)
This study was designed to investigate the dental changes and the space gained following early treatment of pseudo-Class III malocclusion, using a simple fixed appliance. Twenty-one consecutively treated patients who had a pseudo-Class III malocclusion comprised the treated group. Fifteen untreated control subjects were used as matched controls for the three-year follow-up after completion of treatment. Lateral cephalograms and study models were analysed for the treated, the control and the follow-up group. The arithmetic mean and standard deviation were calculated for each variable, and paired t-tests were performed to assess the effects of treatment on the treated group. The Mann-Whitney test was performed to evaluate the difference between the follow-up group and the control group. Anterior crossbites and mandibular displacements were eliminated after the treatment. On average, the space gained as a result of the treatment was 4.7mm in the upper arch (p<0.001°). Comparison of the space available as a result of early treatment with the space required for alignment of posterior segments in the upper arch of the untreated control group indicated that there was enough space for the eruption of the canines and premolars as a result of early treatment; whereas, lock of space was evident in the untreated controls. In conclusion, a pseudo-Class III malocclusion, proclination of the upper incisors and/ or retroclination of the lower incisors contributed to the correction of anterior crossbite and the elimination of mandibular displacement. Proclination of the upper incisors, utilisation of leeway space, and arch-width increase provided the space required for eruption of the premolars and canines.